2014
DOI: 10.1016/j.nanoen.2014.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-based hybrid cell for harvesting solar energy and raindrop electrostatic energy

Abstract: Silicon-based solar cell is by far the most established solar cell technology. The surface of a Si solar cell is usually covered by a layer of transparent material to protect the device from environmental damages/corrosions. Here, we replaced this protection layer by a transparent triboelectric nanogeneartor (TENG), for simultaneously or individually

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
144
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 242 publications
(148 citation statements)
references
References 34 publications
2
144
1
1
Order By: Relevance
“…135 Aer this architecture was proposed, various hybrid energy harvesters were suggested and demonstrated using acoustic waves and pressure for the piezoelectric effect, which were based on PVDF TENG-based multi-type energy harvesters have also received great attention because of their high output power and easy hybridization with other energy harvesters. [139][140][141][142][143][144] In 2013, Yang et al demonstrated a hybrid energy harvester based on the triboelectric effect and the PV effect for the rst time. Micropyramid Si solar cells were fabricated with a protective layer consisting of a thin lm of polydimethylsiloxane (PDMS) nanowires, which not only worked as a protective layer, but also as a triboelectric layer for harvesting mechanical energy ( Fig.…”
Section: Integration Of Various Energy Harvestersmentioning
confidence: 99%
“…135 Aer this architecture was proposed, various hybrid energy harvesters were suggested and demonstrated using acoustic waves and pressure for the piezoelectric effect, which were based on PVDF TENG-based multi-type energy harvesters have also received great attention because of their high output power and easy hybridization with other energy harvesters. [139][140][141][142][143][144] In 2013, Yang et al demonstrated a hybrid energy harvester based on the triboelectric effect and the PV effect for the rst time. Micropyramid Si solar cells were fabricated with a protective layer consisting of a thin lm of polydimethylsiloxane (PDMS) nanowires, which not only worked as a protective layer, but also as a triboelectric layer for harvesting mechanical energy ( Fig.…”
Section: Integration Of Various Energy Harvestersmentioning
confidence: 99%
“…Recently, triboelectric nanogenerator (TENG) based on contact-electrification [13][14][15] was developed to harvest water energy from various energy form, such as ocean waves [16], flowing water [17,18] and raindrops [16,19,20]. Essentially, TENGs [8,9] harvest ambient energy by means of the contact and separation of two materials.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, water-solid interaction also causes triboelectricity with the formation of an electrical double layer (EDL) [28][29][30][31][32]. Using water as a charging material directly, a TENG can harvest water energy (water-TENG) based on a fairly simple structure consisting of one electrode and one solid material [19,20]. With a transparent polymer surface and a single electrode, the water-TENG can successfully cause light to penetrate to a solar cell [20].…”
Section: Introductionmentioning
confidence: 99%
“…Electrocoalescence and breakups of drops are an important research subject in climate science [40,41] as well as in the dehydration process of crude oil [42,43]. Liquid contact electrification charging of drops can be employed in portable energy harvesting devices [44][45][46][47][48][49][50]. Understanding of the charged droplet behavior under electric field is critical in electrospray mass spectrometry [51][52][53][54] and electrohydrodynamic (EHD) printing technology [55,56].…”
Section: J Immentioning
confidence: 99%
“…In surface science, controlling the surface charge on a droplet by chemical or physical methods is an interesting topic [93,94]. Besides, the droplet charging by liquid-solid contact electrification has been actively reported as a novel energy harvesting method [44][45][46][47][48]95]. In physics, droplet behavior under electric field is one of the major concerns of classical electrohydrodynamics [27,[96][97][98].…”
Section: Fundamentals and Applicationsmentioning
confidence: 99%